Analisis Keberhasilan Rehabilitasi Hutan Dan Lahan Di Sub Das Miu - Mursalim Mursalim; Akhbar Akhbar; Hasriani Muis (Universitas Tadulako, 2019)
The study aims to identify changes in forest cover resulting from forest and land rehabilitation activities using Landsat 8 OLI Imagery in Miu Sub Watershed Area and to formulate the role of the parties to the implementation of forest and land rehabilitation in the Miu Sub Watershed. This research was conducted in Miu Sub Watershed area in Sigi, Central Sulawesi. This research was conducted for 4 months starting from June until September 2017. Data obtained through direct observation to the field, while the role of the parties obtained through the method of purposive sampling. The data were processed using analysis of image interpretation and 4R analysis for the role of the parties. The results show that the success rate of forest and land rehabilitation in the Miu Sub Watershed area is included in either good category until very good. From the result of wide delineation of landsat image 8 it is known that the Miu Sub Watershed area in Namo village has the highest percentage in the implementation of forest and land rehabilitation management of 92% with an area of ​​50 Ha. While the results of 4R analysis indicate that the relevant parties have performed their duties and responsibilities fairly well so that forest and land rehabilitation activities in the Miu Sub Watershed area could be done well.